Revision of the genus Exochomoscirtes Pic (Coleoptera: Scirtidae: Scirtinae) - Ruta, Rafał; Yoshitomi, Hiroyuki (Zootaxa, 2010)
The genus Exochomoscirtes Pic is redefined and Exochomoscirtes binotatus Pic, 1916 is designated the type species of the genus. A detailed redescription of the genus is provided. The larva of Exochomoscirtes is described for the first time. Exochomoscirtes immaculatus Pic, 1930 is transferred to Scirtes. Ora discoidalis Pic, Scirtes bipustulatus Champion, S. ephippiatus Champion, S. maculatus Waterhouse, S. retusus Champion, S. ruforotundus Watts, S. sphaericus Champion, S. tetrastigma Champion, and S. maculatus Waterhouse are transferred to Exochomoscirtes. Exochomoscirtes bimaculatus Pic, E. binotatus Pic, E. discoidalis (Pic), E. ephippiatus (Champion), E. maculatus (Waterhouse), E. rufomaculatus Pic, E. sphaericus (Champion), and E. tetrastigma (Champion) are redescribed. Twenty three new species are described, including Exochomoscirtes arunahalensis sp. nov. (India), E. basipunctatus sp. nov. (Borneo), E. bezdeki sp. nov. (Laos), E. buechei sp. nov. (Sulawesi), E. cambodiensis sp. nov. (Cambodia), E. ceylonicus sp. nov. (Sri Lanka), E. dilaticornis sp. nov. (Borneo), E. globosus sp. nov. (Sumatra), E. jaechi sp. nov. (Thailand), E. klausnitzeri sp. nov. (Java, Borneo, Sumatra, Thailand, Laos), E. longispinus sp. nov. (Borneo), E. luteosuturalis sp. nov. (Sulawesi), E. luteosuturaloides sp. nov. (Borneo, Vietnam), E. meghalayensis sp. nov. (India), E. nahangensis sp. nov. (Vietnam), E. nigromarginatus sp. nov. (Malayan Penins.), E. nipponicus sp. nov. (Japan), E. pectinatus sp. nov. (Borneo), E. picturatus sp. nov. (Borneo), E. quadripartitus sp. nov. (Malayan Penins.), E. takizawai sp. nov. (Borneo), E. thailandicus sp. nov. (Thailand) and E. serricornis sp. nov. (Malayan Penins.). Thirty five species of Exochomoscirtes are presently recognized. A key is given to the species.